KONSEP TRANSMEDIA STORYTELLING PADA IKLAN CETAK MOBIL VOLKSWAGEN DENGAN MEDIA AUGMENTED REALITY - Ardhariksa Zukhruf Kurniullah (Universitas Bunda Mulia, 2016)
New media or convergence, in a few years we often hear, especially the convergence of media that are often associated with new media that is now developing, particularly media-related technology development. The rapidly of media convergence growthto advances in technology these days, especially when the advent of the Internet and the digitization of information. This media convergence brings together the name